Microstructural, mechanical and thermal characteristics of zirconia-based thermal barrier coatings deposited by plasma spraying. Issue 9 (November 2015) - Di Girolamo, G.; Blasi, C.; Brentari, A.; Schioppa, M.
Abstract: Ceramic thermal barrier coatings (TBCs) are potential tools to increase the durability of metal parts operating in turbine engines. In this work, partially yttria stabilized zirconia (YSZ) and lanthanum zirconate (LZ) coatings were deposited by plasma spraying on stainless steel substrates. X-Ray Diffraction (XRD) analysis revealed that plasma spraying promoted the formation of metastable phases in both the cases. Both YSZ and LZ coatings exhibited porous microstructure with a network of embedded pores and microcracks, that resulted in similar porosity values. The average microhardness of LZ coating was about 92% of that of YSZ one (5.4 against 5.9 GPa), whereas the thermal expansion coefficient (CTE) of LZ coating was about 86% of that of YSZ one. Based on the results herein discussed the development of multilayered microstructures represents a promising solution in order to develop TBCs with enhanced performance.